Variations of macro- and microelements in yellow-fleshed cassava (Manihot esculenta Crantz) genotypes as a function of storage root portion, harvesting time, and sampling method - Alamu, Emmanuel Oladeji; Maziya-Dixon, Busie; Sibeso, Consent; Parkes, Elizabeth; Dixon, Alfred Gilbert (MDPI, 2020)
The correct estimation of the mineral content of cassava (Manihot esculenta) genotypes is vital from a nutritional point of view. This study evaluated the effects of the storage root section, maturity, and sampling method on the macro- and microelements in yellow-fleshed cassava root genotypes. In total, 44 genotypes were grown in replicated field trials of 2 sets (set 25 and set 19) and were harvested at 9 and 12 months after planting. Two sampling methods, sampling with a cork borer (A = proximal, B = middle, C = distal or method 1) and sampling without a cork borer (L = Longitudinal or method 2), were used. The minerals of the samples from the two methods were determined using inductively coupled optical emission spectrometry (ICP-OES). K and Mn were the most abundant minerals, and Na, Mo, and Co were the least abundant. Genotype, method, and maturity had a strong influence on mineral concentrations. Harvesting time affected the concentration level of some macro- and microelements in cassava roots. Additionally, Ca, Mg, K, P, Mn, Cu, Ni, and Zn contents were significantly (p < 0.05) higher in the proximal and middle portions for method 1. K and P and Mn and B were positively correlated, but K and Na and Fe and Ni were negatively associated.